Особливості добровільного колективного управління майновими авторськими та (або) суміжними правами: нормативно-правове регулювання та практика його впровадження - Костів, Олександр; Kostiv, Oleksandr (ЗУНУ, 2021)
Стаття присвячена дослідженню особливостей добровільного колективного управління майновими авторськими та (або) суміжними правами, нормативно-правовому регулюванню зазначеної сфери відносин та практиці його впровадження. Проаналізовано вимоги до організацій, які можуть здійснювати добровільне управління, а також правові підстави набуття ними прав на здійснення такого управління. Встановлені також відмінності між добровільним та розширеним і обов’язковим колективним управлінням. The article is devoted to the research of the peculiarities of voluntary collective management of property copyrights and (or) related rights, normative legal regulation of the specified sphere of relations and practice of its implementation. The requirements to the organizations which can carry out voluntary management, and also the legal bases of acquisition by them of the rights to implementation of such management are analyzed. The differences between voluntary and extended and compulsory collective management are established. During the research, the following conclusions are made: After the adoption of the special Law of Ukraine “On effective management of property rights of copyright holders in the field of copyright and (or) related rights” voluntary management has become one of the three types of collective management; Its implementation takes place on a contractual basis exclusively in respect of property rights, which are transferred by the right holders to the management and included in the relevant catalogs of organizations; Voluntary management is carried out by a public association with the status of a legal entity, registered in a non-profit institution, founded exclusively by right holders, whose activities are aimed at collective management of property rights to copyright and (or) related rights; Areas covered by voluntary management include all areas except those designated for compulsory and extended management. Moreover, the spheres of voluntary and extended management may overlap; An important guarantee for the right holder is the introduction by the legislator of the right to revoke property rights from management in whole or in part. Thus, a competitive market between organizations is formed. This will increase their efficiency; To restore the definition of a collective management agreement, which was removed from the law on copyright but not included in the law on effective management, we propose to supplement Art. 1 by the specified definition. Accordingly, the collective management agreement is proposed to be understood as an agreement that regulates the relationship between right holders and relevant collective management organizations, which authorize managers to act on their behalf in relations with users of the objects of intellectual activity on: approval of the amount of remuneration, conclusion of agreements with users on the use of rights transferred to management; collection, distribution and payment of the collected remuneration for the use of such objects to the right holders whose rights they manage; taking actions necessary to protect the rights managed by the organization of collective management, including going to court to protect the rights of right holders in accordance with the statutory powers and instructions. Further development of research in the field of voluntary governance may involve a clearer definition of the legal and procedural status of organizations that manage rights.
Peculiarities of voluntary collective management of property copyrights and (or) related rights: normative legal regulation and practice of its implementation
Keywords: авторське право і суміжні права; колективне управління; добровільне колективне управління; правовласник; copyright and related rights; collective management; voluntary collective management; right holder